Emerging Low‐Dimensional Crystal Structure of Metal Halide Perovskite Optoelectronic Materials and Devices. Issue 6 (24th March 2021) - Chu, Zema; Chu, Xinbo; Zhao, Yang; Ye, Qiufeng; Jiang, Ji; Zhang, Xingwang; You, Jingbi
Abstract : Metal halide perovskites with 3D crystal structures have been attracting widespread attention in the past decade for their outstanding optoelectronic properties and applications. The emergence of low‐dimensional perovskites, which have been successfully demonstrated in varying electronic and optoelectronic applications, offers a number of advantages compared with 3D counterparts due to their tunable and diverse properties. Herein, at first, it is focused on the fundamental understanding about the crystal structure and the unique optical and electronic properties of low‐dimensional perovskite, which are addressed in comparison with 3D perovskites. Moreover, recent developments in application using low‐dimensional perovskite, especially in layered perovskites, are summarized, including solar cells, light‐emitting diodes, photodetectors, lasers, and white‐light emissions, where the main strategies and parameters for enhancing materials properties and the devices performance in varying application are addressed. Finally, the perspectives for the current challenges and the future opportunities of low‐dimensional perovskites are discussed to provide a roadmap to the development in the future. Abstract : Low‐dimensional perovskites have been successfully demonstrated in varying electronic and optoelectronic applications. Herein, the crystal structures, the unique optoelectronic properties, and recent developments in applications of low‐dimensional perovskites are addressed. It offers better understanding the relations between structures and properties, and open more possibilities for widespread optoelectronic applications based on low‐dimensional perovskites in the future.